The story of art - Gombrich, E. H. (Ernst Hans), 1909-2001. (London : Phaidon Press, Ltd., 1995)
The Story of Art is one of the most famous and popular books on art ever published. For 45 years it has remained unrivalled as an introduction to the whole subject, from the earliest cave paintings to the experimental art of today. Readers of all ages and backgrounds throughout the world have found in Professor Gombrich a true master, who combines knowledge and wisdom with a unique gift for communicating directly his own deep love of the works of art he describes.
The Story of Art owes its lasting popularity to the directness and simplicity of the writing, and also the author's skill in presenting a clear narrative.
He describes his aim as 'to bring some intelligible order into the wealth of names, periods and styles which crowd the pages of more ambitious works', and using his insight into the psychology of the visual arts, he makes us see the history of art as 'a continuous weaving and changing of traditions in which each work refers to the past and points to the future', 'a living chain that still links our own time with the Pyramid age'.
In its new format, the 16th edition of this classic work is set to continue its triumphant progress for future generations and to remain the first choice for all newcomers to art.
28. A Story Without End: The triumph of Modernism.
Includes bibliographical references and index.
Keywords: Art -- History